Analysis, appraisal and improvement on airbag sensor assembly line - Cao, Zhe (2014)
To stay competitive in the fast-changing and high-technology era, world-famous companies like Delphi Automotive System Singapore choose to automate the production line to cut cost on labor and reduce process variation. Although as a leader in operation and manufacturing excellence, it is eager to exploit room for improvement in the areas of sensors, robot manipulators, and tool design.